Perceived barriers and facilitators to uptake of non‑traditional roles by pharmacists in Saudi Arabia and implications for COVID‑19 pandemic and beyond: a qualitative study using Theoretical Domain Framework - Eeman Mohammed; Saval Khanal; Zahraa Jalal; Ejaz Cheema; Mohammed H. Abutaleb; Vibhu Paudyal (Taylor & Francis Group, 2021)
Background The COVID-19 pandemic has further strengthened the need for pharmacists to uptake non-traditional roles. Pharmacy practice in Saudi Arabia is emerging in recent years with greater policy emphasis on pharmacists taking new clinical roles. This study aimed to explore the experiences, perceptions and barriers of Saudi pharmacists about their uptake of non-traditional roles using Theoretical Domains Framework (TDF). Methods A qualitative semi-structured study using face-to-face or telephone interviews were conducted. Eligible participants included qualified pharmacists from Saudi Arabia. Interviews focused on pharmacist's perceptions, current opportunities and key challenges towards the uptake of non-traditional roles. Interviews were audiotaped and transcribed verbatim. Results were analysed through the framework analysis method and were later mapped with respective domains of TDF. Results A total of 14 pharmacists completed the interview (9 females and 5 males). Participants showed an overall positive attitude towards the uptake of non-traditional roles. Participants felt that there was wider support available for pharmacists at the policy level to uptake non-traditional roles. However, a need for greater recognition of roles by other healthcare professionals and patients were identified. Participants alluded to reluctance of some physicians to take on board the suggestions from a pharmacist. Key barriers to uptake of non-traditional roles were related to environmental context and resources domain of TDF. For example, participants discussed the need for even further practical experiences during their undergraduate degree to become ready to adopt non-traditional roles in clinical practice. Conclusions Participants of this theoretically informed qualitative study showed an overall positive attitude towards the way pharmacy practice is progressing in Saudi Arabia and their uptake of non-traditional roles. However, there is a need to improve interdisciplinary working, patient awareness of pharmacist competencies and their educational preparedness in furthering their uptake of non-traditional roles. Addressing such barriers and promoting uptake of novel roles by pharmacists is imperative in the context of emerging COVID-19 and future pandemics.